Straightlining prevalence across domains of social media use and impact on internal consistency and mental health associations in the LifeOnSoMe study - Jens Christoffer Skogen; Amanda Iselin Olesen Andersen; Gunnhild Johnsen Hjetland; Leif Edvard Aarø; Ian Colman; Børge Sivertsen; Turi Reiten Finserås (Scientific Reports)
Abstract Straightlining (uniform responses across items), poses a risk in surveys. Among adolescents, previous studies have investigated the prevalence and impact of straightlining in shorter questionnaires within larger surveys. A typical finding is that straightlining is more common among younger respondents, and particularly among boys. A better understanding of straightlining is important for improving data quality. The present study aims to estimate the prevalence of straightlining among adolescents filling out a survey covering different aspects of social media use across 64 items. Additionally, it seeks to assess the impact of straightlining on internal consistency and the associations between six domains of social media use and symptoms of anxiety and depression. Data from the «LifeOnSoMe»-study (N = 3,285), collected from adolescents (aged 16+) in Bergen, Norway. Descriptive and inferential statistics. In total, 5.4% of participants were straightliners, (8.6% of the boys vs. 2.9% of the girls (p < 0.001)). There were no differences in age between straightliners and the remainder of the sample. Overall, the prevalence and impact of straightlining was limited in the present sample. However, there were large discrepancies in terms of both internal consistency, correlations between domains of social media use, and associations with symptoms of anxiety and depression between straightliners and the remainder of the sample. Straightlining behavior had minimal effects on this sample’s analytical epidemiological conclusions. While boys were more prone to straightlining than girls, overall prevalence was low. However, significant discrepancies between straightliners and other respondents suggest potential risks in samples with higher straightlining prevalence.